An Effect of Fucoidan Extract from Sargassum Siliquosum Using Combined Ultrasonic & Enzymatic Method on Its Functional Properties - Abdullah, Asadaldin; Puspasari, Ifa (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Fucoidan is a Sulfated polysaccharide derived from brown seaweed, it has attracted considerable attention due to its various biological properties. Indonesia has riches diversity biological abundant sea. One of areas in the Special Region of Yogyakarta Province that have potential producing algae is Regency Gunung Kidul. The extracted fucoidan from brown algae using conventional method depends on dissolution wall cell polysaccharide in various conditions, such as hot water, acids /alkalis, and organic solvents. However, the approach this own shortcomings, namely time long extraction and results low yield. For overcome this problem, this study evaluates the effectiveness of combined ultrasound and enzyme extraction method in improving the yield and bioactive properties of fucoidan obtained from Sargassum Siliquosum. Cellulase enzyme concentrations (0.5%, 1%, and 2% v/v) were investigated and compared with the conventional extraction method. The result showed that the (UAE+EAE 2%) method provided the highest yield (3.622%), which is higher than the conventional method (3.506%), while the lower enzyme concentrations produced less yields. FTIR analysis ensured that the functional groups of fucoidan, including sulfate ester (S=O) and glycosidic (C-O-C) bonds. The effective extraction of fucoidan was confirmed by High Performance Liquid Chromatography (HPLC) analysis, and the DPPH assay's evaluation of antioxidant activity showed that the bioactive characteristics of fucoidan were maintained. Overall, in comparison to conventional extraction methods, the combined UAE+EAE approach shows great promise as a more effective and eco-friendlier fucoidan extraction technology. Further optimization and purification for the extracted fucoidan are recommended to improve bioactivity for future applications.